Effect the Magnetic Water on Physiological Traits of Callus the Fenugreek (Trigonella foenum graecum L.) - Basheer Abdulhamza Alalwani (Journal of Global Pharma Technology, 2020)
The experiment was conducted in the tissue culture lab. Biology Dept., Babylon University. Callus induction was achieved by culturing the seeds of (Fenugreek) Trigonella foenum-graecum (L.) on MS medium supplemented with 1.0 mg/lˉ¹ 2, 4-D and BA which combination with all study treatments'. The magnetic water effected by improving the growth of callus, physiological and biochemical characteristics of callus. This study aimed to investigate the effects of magnetic water on some characteristics of growth and chemical constituent in Fenugreek. To this end callus formation was allowed to take place for 45 days in the dark at 25±2 °C from Fenugreek seeds were grown as two experimental groups. A group of seeds were irrigated with distilled water and in parallel the other group with magnetic water at three gausses 1000, 2000 and 3000 gauss. Results revealed that in comparison to control plants, irrigating with magnetic water increases the growth parameters. The treatments 1000 and 2000 gauss showed significant increase in fresh and dry weight, but decline was at 3000 gauss overcome of all treatments including control (Distilled water). From the results obtained it can be said that Physiological Traits outperformed on control by gave the highest values of CAT and SOD by using of magnetic water. Keywords: Fenugreek (Trigonella), Tissue cultures, Magnetic water.